Reflections on Anti-Reflection Coatings - Chou, B.R. (Canadian Journal of Optometry, 1983)
Recently several ophthalmic suppliers have advertised lines of spectacle lenses with anti-reflection coatings. In this paper, the need for antireflection coatings and the underlying optical principles are reviewed, and manufacturers' claims are critically examined.